2017
DOI: 10.1111/jfbc.12487
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of bacterial quorum sensing signals in spoilage potential ofAeromonas veroniibv.veroniiisolated from fermented surimi

Abstract: This study characterized the spoilage potential of the N-acyl homoserine lactone (AHL)-producing strain, Aeromonas veronii bv. veronii, isolated from fermented surimi, and investigated the effects of exogenous AHLs on its spoilage characteristics. The strain showed a strong ability of producing total volatile base nitrogen (TVB-N) and putrescine, and four types of AHLs, including N-butanoyl-L-homoserine lactone (C4-HSL), N-hexanoyl-L-homoserine lactone (C6-HSL), N-heptanoyl-Lhomoserine lactone (C7-HSL), and N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
3
8
0
Order By: Relevance
“…Most of the isolates (QS7‐4, QS20‐8, QS20‐11, QS24‐2, QS24‐6, QS24‐17, QS24‐20, QS24‐21, and QS36‐2) produced C4‐HSL, N ‐butyryl L ‐homoserine lactone. This type of AHL was reported earlier in plant‐associated bacteria such as A. veronii ; A. hydrophila ; A. caviae ; Enterobacter asburiae ; P. aeruginosa ; P. sihuiensis . The phylogeny of the elite biofilm‐forming bacteria reported in the present study belongs to species of Aeromonas ( A. hydrophila , A. enteropelongenes , A. veronii ), E. cloacae , Providentia rettgeri , K. pneumoniae , S. aquatilis , P. sihuiensis , and K. cowanii .…”
Section: Discussionsupporting
confidence: 88%
“…Most of the isolates (QS7‐4, QS20‐8, QS20‐11, QS24‐2, QS24‐6, QS24‐17, QS24‐20, QS24‐21, and QS36‐2) produced C4‐HSL, N ‐butyryl L ‐homoserine lactone. This type of AHL was reported earlier in plant‐associated bacteria such as A. veronii ; A. hydrophila ; A. caviae ; Enterobacter asburiae ; P. aeruginosa ; P. sihuiensis . The phylogeny of the elite biofilm‐forming bacteria reported in the present study belongs to species of Aeromonas ( A. hydrophila , A. enteropelongenes , A. veronii ), E. cloacae , Providentia rettgeri , K. pneumoniae , S. aquatilis , P. sihuiensis , and K. cowanii .…”
Section: Discussionsupporting
confidence: 88%
“…Specific spoilage organisms (SSOs) play a crucial role in this process. Recent studies have indicated that bacterial spoilage may be regulated by a cell density-dependent communication mechanism called quorum sensing (QS), which is based on the self-secretion and detection of QS signaling molecules (Fuqua et al, 1994; Gui et al, 2017; Zhao et al, 2017). Bacteria trigger the expression of factors required for food spoilage (such as extracellular proteases, lipases, pectases, and cellulases) or pathogenesis (such as biofilm formation, motility alteration, hemolysin production, and pyocyanin generation) when the concentration of these signaling molecules reaches a certain threshold level (Bai and Rai, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Vibrio harveyi typically employs secreted harveyi autoinducer-1 (HAI-1), autoinducer-2 (AI-2), and cholerae autoinducer-1 (CAI-1) as signaling molecules (Galloway et al, 2011; Defoirdt, 2017). Recent studies have found that the above signaling molecules are often detected in contaminated aquatic products (Li et al, 2016; Zhao et al, 2017). Accordingly, additional work is still needed to explore the potential relationship between signaling molecule-based QS system and food spoilage.…”
Section: Introductionmentioning
confidence: 99%
“…Various Aeromonas species is widely distributed in the aquatic environment and is commonly recognized as spoilage organisms in seafood, mainly in fish and crustaceans from tropical or warmer waters [11]. The spoilage potential of a particular microorganism is the result of the ability to produce the metabolites that are associated with the spoilage of a product [175], and the determination of the actual spoilage potential requires a combination of sensory, microbial and chemical analyses [176]. A. salmonicida (including psychrophilic strains responsible for causing the fish infection furuncluosis) is one of the most highlighted Aeromonas species regarding seafood spoilage.…”
Section: Aeromonas As a Spoilage Organism In Seafoodmentioning
confidence: 99%
“…were identified as part of the dominating microbiota in spoiled grass carp ( Ctenopharyngodon idellus ) [181] and the species A. allosaccharophila , A. eucrenophila and A. rivipollensis were isolated from spoiled silver carp ( Hypophthalmichthys molitix ) fillet during storage at 4 °C [182]. A strain of A. veronii biovar veronii was characterized as a potential spoiler of fermented surimi as it produced a high level of total volatile basic nitrogen (TVB-N) and putrescine [176]. Aeromonas isolates associated with spoilage in fish and meat were characterized as slime producers, and 95% of the isolates showed lipase activity and protease activity [183].…”
Section: Aeromonas As a Spoilage Organism In Seafoodmentioning
confidence: 99%